Using Snapchat in the process of teaching learning and learning as interculturality tool / O uso do Snapchat no processo de ensino aprendizagem de LI como ferramenta de interculturalidade - Gêrlan Cardoso da Silva (Universidade Estadual de Alagoas, 2017)
Teaching a foreign language involves more than the morphological aspects present in it, because the structure of a language is composed of the presence of sociocultural factors and must be presented to the student for a concrete acquisition of it and not only the representation of a part of it. The objective was to carry out a qualitative and bibliographical research where it is reflected on the teaching of English language learning through an application called Snapchat that brings interculturality situations in its programming. Currently, theorists defend the use of communicative approaches in discussion about the old teaching of foreign languages decontextualized and demotivating. This article is based on a qualitative and bibliographical research referenced in the view of the process of Teaching English Language Learning as a presupposition of immersing the student in it, through social, economic, political and cultural aspects that permeate a Foreign Language through an application called Snapchat. Authors such as: ALMEIDA (2007); BRASIL (1999); MOURA (2005); RAJAGOPALAN (2003); UNESCO (2009) and others supported the work by bringing the debate about the subject of LI teaching, but contextualized and on the importance of interculturality.